Potential biochemical markers of epilepsy - Marina Yu. Maksimova; Ekaterina M. Abbasova; Anna D. Shitova (Анналы клинической и экспериментальной неврологии)
The diagnosis of epilepsy and assessment of the frequency and severity of seizures are essential for the treatment of patients. Epileptogenesis monitoring at different stages can be beneficial in assessing the efficacy of antiepileptic therapy. This approach relies on the concept of biomarkers. A subset of these biomarkers may possess not only diagnostic value but also prognostic value, which is defined as the ability to predict the nature of the epilepsy course and the probability of recurrent seizures.